On the anisotropy of shear fracture toughness in rocks. (June 2021) - Nejati, Morteza; Bahrami, Bahador; Ayatollahi, Majid Reza; Driesner, Thomas
Highlights: We experimentally analyse the anisotropy of true mode II fracture toughness in rocks. Shear fracture toughness is shown to follow a sinusoidal variation. A simplified relationship between fracture toughness and fracture energy is presented. True mode II fracture toughness is noticeably greater than mode I fracture toughness. The fracture process zone of a true mode II crack is of a semi-elliptical shape. Abstract: Experimental and theoretical analyses are presented that assess true mode II fracture toughness, K IIc, fracture energy, G IIc, and associated fracture process zone (FPZ) in anisotropic rocks. The term true signifies the type of mode II crack that grows in a self-planar manner as a result of shear stresses, and thus differentiates it from a generic mode II crack that often extends by forming a tension-induced kink. We give the theoretical basis for the sinusoidal variation of K IIc, and present simplified relations for the direction dependence of the G IIc in an anisotropic plane. Our experimental data on anisotropic Grimsel Granite validate this theoretical model, thereby providing supporting evidence that K IIc of this rock type indeed follows a sinusoid function. This model takes only two principal values of K IIc to characterise fracture toughness and energy in any direction within an anisotropic plane. Our analyses also show that the values of K IIc and G IIc are noticeably higher than the ones of mode I, and one must distinguish between these toughness values when formulating growth criteria in rocks. Lastly, a thorough analysis of the strain localisation obtained from the digital image correlation data gives insight on the nature of the FPZ, and demonstrates that the FPZ of a true mode II crack is of a semi-elliptical shape and has a comparable size with the one of a mode I crack.